Pseudoscirus gen. nov. of Coleoscirinae (Acari: Prostigmata: Cunaxidae) from the Amazon rainforest, Brazil, with a key to the genera of adult female Coleoscirinae - Rocha, Matheus Dos Santos; Silva, Guilherme Liberato da; Ferla, N. J.; Franklin, E.; Wurlitzer, Wesley Borges (Journal of Natural History, 2021)
The genus Coleoscirus Berlese, 1916, is revised and divided into two genera. Coleoscirus intermedius Corpuz-Raros, 1996 is designated the type species for Pseudoscirus Wurlitzer and Rocha gen. nov. This new genus is peculiar in having characteristics of both Coleoscirus Berlese, 1916 and Pseudobonzia Smiley, 1975. The general characters of Pseudoscirus Wurlitzer and Rocha gen. nov. within the subfamily Coleoscirinae Den Heyer, 1978 include the presence of a small dorsal shield that covers only the propodosoma, and having swollen apices of solenidia on tarsus I. The new genus resembles Coleoscirus species due to coxal plates I and II fused medially, forming the sternal shield, and idiosomal plates poorly developed. A new species from the Amazonic biome in Brazil, Pseudoscirus amazonae Wurlitzer and Rocha sp. nov., is also described and illustrated. The new species differs from the known species Pseudoscirus intermedius Corpuz-Raros, 1996 by basifemora II with 6 sts; propodosomal shield with a notch, and simple tactile setae c1, c2, d1, e1, f1, f2, h1 and h2 on minute sclerotised plates. urn:lsid:zoobank.org:pub:C45C0CF6-CEAB-4AF1-995F-FDCDB2062C3F. © 2021 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: Coleoscirus; Pseudoscirus